Advantages and Disadvantages of Text-Based Language Teaching to Future Pedagogues - Quvanov Azamat Ziyadulla o‘g‘li; Jabbarova Anora Javliyevna (Genius Publishing Group, 2023)
The use of text-based communication for English language teaching has become increasingly popular in recent years. This approach offers several advantages, including greater flexibility, convenience, and accessibility. However, it also has some disadvantages, such as the potential for misinterpretation and the lack of opportunity for real-time interaction and feedback. This paper explores the advantages and disadvantages of text-based English language teaching, drawing on existing research and professional experience.
Keywords: Flexibility; accessibility; cost-effectiveness; synchronous learning